The effect of project success on corporate reputation of the public sector organizations in Pakistan - Hassan, Mazlan; Muhammad Irfan (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
The purpose of this study is to assess the effect of project success on the corporate reputation of the public sector organizations in Pakistan in the light of signaling theory. A cross-sectional survey across Pakistan yielded 425 valid responses. The sample was restricted to respondents registered with Pakistan Engineering Council. Smart PLS version 3.0 was employed to assess the proposed reflective-formative model through path modelling and bootstrapping technique. The results showed that project success is positively related to corporate reputation. This paper provides empirical evidence about the positive effect of project success on the corporate reputation from public sectors’ view, in Pakistan.